To Analyze the Effect of Platelet Count of Platelet-rich Plasma on Clinical Outcomes in Patients of Osteoarthritis of Knee - Amit Saraf; Prakhar Agarwal; Abhinav Kush (Journal of Orthopedics, Traumatology and Rehabilitation)
Purpose: The purpose of this study was to find the association between the platelet (PLT) count in PLT-rich plasma (PRP) injection and clinical response in knee osteoarthritis (KOA) patients. Materials and Methods: Fifty patients of Kellgren–Lawrence Grade 2 and 3 KOA were given single intra-articular PRP injection. Baseline PLT count was documented and PLT concentration of each PRP was documented and was classified as P1, P2, and P3 (as per PAW classification). This was compared to clinical results using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Visual Analog Scale (VAS) score at baseline, followed by 3, 6, and 9 months of follow-up. Results: There was a significant decrease in VAS score between the P1 and P2 and P1 and P3 groups at 9-month follow-up, with P = 0.028 (<0.05) and P = 0.01 (<0.05), respectively. Moreover, the WOMAC score significantly dropped among the P1 and P2 and P1 and P3 groups at 9-month follow-up, with P = 0.016 (<0.05) and P = 0.036 (<0.05), respectively. Conclusion: Both the VAS score and the WOMAC score have significantly decreased at 9-month follow-up period when the P1 group is compared to both P2 and P3 but not between P2 and P3, so it is concluded that for proper efficacy of PRP injection in OA knee Grades 2 and 3, concentration of platelets in prepared PRP should be more than baseline PLT concentration.